Evolving protected-area impacts in Panama: Impact shifts show that plans require anticipation - Haruna, Akiko; Pfaff, Alexander; van den Ende, Sander; Joppa, Lucas (IOP Publishing, 2014)
Protected areas (PAs) are the leading forest conservation policy, so accurate evaluation of future PA impact is critical in conservation planning. Yet by necessity impact evaluations use past data. Here we argue that forward-looking plans should blend such evaluations with anticipation of shifts in threats. Applying improved methods to evaluate past impact, we provide rigorous support for that conceptual approach by showing that PAs' impacts on deforestation shifted with land use. We study the Republic of Panama, where species-dense tropical forest faces real pressure. Facing variation in deforestation pressure, the PAs' impacts varied across space and time. Thus, if shifts in pressure levels and patterns could be anticipated, that could raise impact.